Meaning and Translation: ‘Hand’ in English Translations of the Qur’an - Tansaki, Mohammed Arzka (Journal of Humanities & Social Sciences, 2019)
Translation plays a very important role in propagating the message of the Qur’an since the early period of Islam. As a result, there exist many translations of it into various languages, including English. English language translations of the Qur’an are many and widespread. Many people depend on them to understand the meaning of the Qur’an. However, a careful look at many of these translations reveals their inadequacy in expressing the meaning of many Qur’anic words and phrases with multiple dimensions of meaning. Therefore, this paper tried to critically analyse limited sample of English translations of ‘Yad’ as it appears in the Qur’an. Yad is a basic word that has equivalent in almost every language. It was discovered that, there were problems in the translation of yad when it is used figuratively in the Qur’an; a situation when literal/direct translation, which many of the translators subscribe to was inadequate. Therefore, in translating figurative expressions extra care needs to be taken by the translator.
Keywords: meaning; the Holy Quran; English translation; Hand